Trace-Driven Extension for Noxim Simulator - Pires, Ivan Luiz Pedroso; Alves, Marco Antonio Zanata; Albini, Luiz Carlos Pessoa (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2017: Anais do VII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2017)
Simulation is one of the main tools used to analyze new proposals in the Network-on-Chip (NoC) field. Among these simulators for analyzing and testing new ideas in NoC architectures, the Noxim simulator stands out, being used by many researchers due to the wireless support and open-source availability. An important issue at the simulation phase is the choice of workload, as it may affect testing the system and its features. The correct workload can lead to rapid and efficient system development, while the wrong one may compromise the entire system evaluation. To ensure a more realistic simulation, simulators usually relies on real workloads by using a tracedriven approach. Although Noxim provides a simple support for input traces, it is very limited to a general behavior of the system, accepting only a generic injection rate parameter over time. We propose in this paper an extension of the Noxim simulator to address these issues. This extension enables Noxim to easily receive and process a real workload traces from real applications, considering each message sent by each processing element over the NoC. This extension was demonstrated and evaluated using the NAS-NPB workload. Our results show that Noxim still generating trusty results when using our trace extension.